Law on Khamr Under Qanun Jinayat in Aceh and Brunei Darussalam: A Comparative Study - Muhammad Natsir; Cakra Arbas; Meta Suriyani (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2019)
Drinking khamr (liquor) is an offence under the Criminal Act (Qanun Jinayat) in Aceh and Brunei Darussalam. This paper aims at comparing the law relating to khamr in both jurisdictions. The study was made through content analysis using comparative approach. It is found that both in Aceh and Brunei Darussalam, drinking khamr is subjected to penalty in the form of whipping not exceeding 40 times. The sentence that was adopted from Shariah to be imposed within a trial held by the Shariah Court. Beside similarity, there are some differences especially in relation to the applicability, enforcement and proceedings. The law on khamr in Aceh as stipulated in its Qanun Jinayat is enforced by the Shariah Judge, while the prosecution of drinking khamr in Brunei Darussalam requires the role of prosecutor. Keywords: Drinking Khamr, Criminal Act, Qanun Jinayat and Shariah Court.